2021
DOI: 10.7554/elife.66538
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of a sulfated exopolysaccharide, synechan, and bloom formation in the model cyanobacterium Synechocystis sp. strain PCC 6803

Abstract: Extracellularpolysaccharides of bacteria contribute to biofilm formation, stress tolerance, and infectivity. Cyanobacteria, the oxygenic photoautotrophic bacteria, uniquely produce sulfated extracellular polysaccharides among bacteria to support phototrophic biofilms. In addition, sulfated polysaccharides of cyanobacteria and other organisms have been focused as beneficial biomaterial. However, very little is known about their biosynthesis machinery and function in cyanobacteria. Here, we found that the model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…Only 17 and 14 genes were more highly expressed at 3 h and 24 h, respectively, after the LC shift in Δ cya1 . Several of these genes are situated on the Synechocystis plasmid pSYSM and encode proteins involved in the biosynthesis of extracellular sulfated polysaccharides (Maeda et al ., 2021). Similarly, only nine genes were less strongly induced in Δ cya1 cells placed under LC for 3 h, including the sbtAB operon, however, this difference disappeared after 24 h at LC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 17 and 14 genes were more highly expressed at 3 h and 24 h, respectively, after the LC shift in Δ cya1 . Several of these genes are situated on the Synechocystis plasmid pSYSM and encode proteins involved in the biosynthesis of extracellular sulfated polysaccharides (Maeda et al ., 2021). Similarly, only nine genes were less strongly induced in Δ cya1 cells placed under LC for 3 h, including the sbtAB operon, however, this difference disappeared after 24 h at LC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the absence of Cya1 influences the expression of many genes, including several previously reported to be regulated by the cAMP receptor SyCRP (Yoshimura et al ., 2002). Moreover, the expression of genes encoding proteins involved in the biosynthesis of extracellular sulfated polysaccharides (Maeda et al ., 2021) was altered in Δ cya1 cells, which indicates that cAMP may influence the lifestyle of cyanobacteria. Finally, the concerted upregulation of many transposase‐encoding genes in mutant Δ cya1 points at an important role of this adenylate kinase and/or cAMP in the maintenance of genome stability in Synechocystis .…”
Section: Discussionmentioning
confidence: 96%
“…The availability of several signaling and photoreceptor mutants allows for experimental investigations into how these signals are integrated ( 5 , 19 ). Additionally, the ability to create targeted mutants ( 20 ) makes cyanobacteria a powerful model to test specific predictions about collective behavior. Synechocystis cells can also be modified to express fluorescence markers such as green fluorescent protein (GFP) or yellow fluorescent protein (YFP) ( 21 ), which could be used to monitor subpopulations of cells within a larger group.…”
Section: Advantages Of Cyanobacteria As a Model Experimental System For Collective Behaviormentioning
confidence: 99%
“…The last steps of the EPS biosynthetic pathways are relatively conserved throughout bacteria and often follow one of three major pathways-Wzy-, ABC transporter-or Synthase-dependent-ending with an assembled polymer outside the cell wall [9]. Previously, by performing a phylum-wide analysis, we showed that most cyanobacteria harbor genes encoding proteins related to these pathways but often not a complete set defining one pathway, and the EPS-related genes are scattered throughout the genomes or organized in small clusters, often in multiple copies [1,10,11]. Up until now, the study of the putative EPS-related genes/proteins has been performed, by us and others, mainly through the generation and characterization of knockout mutants using the model cyanobacterium Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%